Normative profiles of neuroretinal rim area in a multiethnic Asian population: the Singapore Epidemiology of Eye Diseases study. Issue 3 (30th November 2020) - Lim, Zhi Wei; Chee, Miao-Li; Lim, Sing Hui; Thakur, Sahil; Majithia, Shivani; Soh, Zhi Da; Teo, Zhen Ling; Rim, Tyler Hyungtaek; Sabanayagam, Charumathi; Tham, Yih-Chung; Cheng, Ching-Yu
Abstract : Aims: To evaluate the normative profiles for neuroretinal rim area (RA) in a multiethnic Asian population. Methods: Subjects were recruited from the Singapore Epidemiology of Eye Diseases (2009–2015) study and underwent standardised examinations. RA measurements were performed using Cirrus high-definition optical coherence tomography (Carl Zeiss Meditec). Multivariable linear regression with generalised estimating equation model was used to evaluate the associations between demographic, systemic and ocular factors with RA. Results: A total of 9394 eyes from 5116 subjects (1724 Chinese, 1463 Malay, 1929 Indian) were included in the final analysis. The mean (±SD) of RA was 1.28 (±0.23) mm 2 for Chinese, 1.33 (±0.26) mm 2 for Malays, and 1.23 (±0.23) mm 2 for Indians. The 5th percentile value for RA was 0.94 mm 2 for Chinese, 0.96 mm 2 for Malay, and 0.89 mm 2 for Indian. In multivariable analysis, following adjustment for age, gender, body mass index, diabetes mellitus, hyperlipidaemia, history of cataract surgery, axial length, intraocular pressure (IOP) and disc area, Indian eyes have smaller RA when compared with Malays (β=−0.074; 95% CI −0.090 to −0.058; p<0.001) and Chinese (β=−0.035; 95% CI −0.051 to −0.019; p<0.001), respectively. Additionally, older age (per decade, β=−0.022), male gender (β=−0.031), longer axial length (per mm, β=−0.025), spherical equivalent (per negative dioptre, β=−0.005), higher IOP (per mm Hg, β=−0.009) were associated with smaller RA (all p≤0.004). Conclusion: In this multiethnic population-based study, we observed significantly smaller RA in Indian eyes, compared with Chinese and Malays. This indicates the need of a more refined ethnic-specific RA normative databases among Asians.